Status of Archives' Digitization at the National Archives of Pakistan - Manan Hafeez , Muhammad Arshad (IJoLIS, 2024)
Purpose: The amin purpose of this study was to explore the current prospects of the archives digitizaiton at the National Archives of Pakistan